علاقة الفكر السياسي بالهوية الثقا والأدبية للأقليات في اجتمع الليبي (1988-1987) دراسة تحليلية في فكر ابت خلدون - Abdulfatah A M Genbij (Universiti Sains Islam Malaysia, 2024)
This study is an important aspect of political and Society minorities into Libya Society through a brief between “1977-1987”.and the problem is the study about the relationship political Thought systems between The Regime and Culture identity. The legality of the impact on the others and consult ben khaledun political Theory and structure State and Science of Sociology, and the study aims to impact political thought of the Government into Culture identity in Libya society and relationship analysis of political Thought in minorities culture identity in Libya Society and knowing how Evolution political thought in Libya Society. The study pursued the descriptive approach as well as the analytical approach for analyzing the study. It also used the comparative approach whenever necessary. The study found several results, most notably, faith in Multiculturalism is reflexive of Culture identity complex society Libyan, impacted relationship in support the Democracy, the obliterating of minorities results of the Totalitarian.